SCOR Based Performance Analysis of Supply Chain Management in Construction Projects - I Dewa Ayu Winda Ari Pramesti Pramesti; Gusti Ayu Putu Candra Dharmayanti; Anak Agung Diah Parami Dewi (Jurnal Ilmiah Telsinas, 2026)
The construction industry heavily relies on highly efficient supply chain management (SCM) to ensure project success, minimize costs, and guarantee timely delivery. This study evaluates the supply chain performance of a construction project at PT. Bingkai Langit Construction, which experienced material procurement constraints. The objective is to measure performance using the SCOR 12.0 framework and formulate improvement strategies.  Using a descriptive analysis method, this study evaluates five SCOR indicators: Reliability, Responsiveness, Agility, Cost, and Asset Management. Data were collected through observations and questionnaires from 37 respondents, analyzed using the Frequency Index method, and finalized via a Focus Group Discussion (FGD) with the strategic management team.  The results show an overall "Good" performance score of 76.8%. Individual indicators scored: Reliability (79.73%), Cost (77.70%), Responsiveness (76.13%), Agility (75.45%), and Asset Management (75.00%). To address weaknesses in asset management and agility, priority strategies include implementing Just-In-Time (JIT) delivery for structural materials, optimizing heavy equipment utilization, reducing material waste, and aligning logistics schedules.